Suicidal Ideation in Malaysian Young Adults: The Role of Depressive Symptoms and Perceived Problem-Solving Ability - Wu, Shin Ling; Sin, Yong Chy (Makara Journal of Health Research, 2024)
Background: The escalating suicide rates among young adults, including those in Malaysia, necessitate a deeper understanding of the factors contributing to suicidal ideation. This study investigates the relationship between depressive symptoms and perceived problem-solving ability, including problem-solving confidence, approach-avoidance style, personal control of emotion, and suicidal ideation among Malaysian young adults. Methods: A total of 231 Malaysian young adults aged 18 to 25 years (Mean = 21.1; SD = 1.38) participated in a cross-sectional survey study. The sample was primarily composed of participants of Chinese ethnicity. Using an online survey, participants completed measures including the Depression, Anxiety, and Stress Scale (DASS-21) depression subscale, Problem-Solving Inventory, and Yatt Suicide Attitude Scale (YSAS). Results: Pearson correlation analysis revealed significant relationships between depressive symptoms, perceived problem-solving ability (specifically problem-solving confidence, approach-avoidance style, and personal control of emotion), and suicidal ideation. Further analysis through logistic regression revealed that young adults with suicidal ideation exhibited a higher likelihood of experiencing depressive symptoms and lower confidence in problem-solving compared to those without suicidal ideation. Conclusions: These findings highlight the importance of addressing depression and promoting effective problem-solving skills as significant strategies to reduce suicidal risk among young adults. Suicide prevention initiatives should prioritize interventions aimed at improving mental well-being and bolstering problem-solving ability in this vulnerable population.